2020
DOI: 10.1155/2020/8539148
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Cardioprotection of YangXinDingJi Capsule against Myocardial Ischemia in Rats

Abstract: Background. YangXinDingJi (YXDJ) capsule is one of traditional Chinese medicines (TCMs) derived from Zhigancao decoction, which is usually used for the treatment of cardiovascular disease in China. Aim of the Study. Cardiovascular events are one of the leading causes of death worldwide. Myocardial ischemia (MI) severely reduces myocyte longevity and function. The YangXinDingJi (YXDJ) capsule has been used in the treatment of clinical cardiac disease in China. Nevertheless, the underlying cellular mechanisms fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…20 Recent studies have reported that LQ exerts cardioprotective effects by attenuating oxidative stress injury, reducing the expression of inflammatory factors, inhibiting cell apoptosis, restoring cardiac functional parameters and maintaining structural integrity. [21][22][23] In addition, many traditional Chinese medicine formula containing LQ have been used to treat cardiovascular diseases, especially ischemic heart disease, such as Zhigancao Decoction, 24 Xuefu Zhuyu Decoction, 25 Yangxin Dingji Capsule, 26 etc. However, the effect of LQ on MI-induced damage remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…20 Recent studies have reported that LQ exerts cardioprotective effects by attenuating oxidative stress injury, reducing the expression of inflammatory factors, inhibiting cell apoptosis, restoring cardiac functional parameters and maintaining structural integrity. [21][22][23] In addition, many traditional Chinese medicine formula containing LQ have been used to treat cardiovascular diseases, especially ischemic heart disease, such as Zhigancao Decoction, 24 Xuefu Zhuyu Decoction, 25 Yangxin Dingji Capsule, 26 etc. However, the effect of LQ on MI-induced damage remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic heart disease (IHD) is one of the leading causes of death and disability globally [ 1 , 2 ]. Although there are many novel therapeutic interventions available for myocardial ischemia treatment, the mortality and morbidity rate are increasing [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, extracts from Glycyrrhiza uralensis suppressed doxorubicin-induced apoptosis in H9C2 rat cardiac myoblasts [ 30 ] and protected the heart against doxorubicin-induced cardiotoxicity [ 31 ]. In fact, many traditional medicine formulas containing LIQ have been used to treat cardiovascular diseases, particularly ischemic heart diseases, such as Si-Miao-Yong-An decoction [ 32 ], Xuefu Zhuyu decoction [ 33 ], YangXinDingJi capsule [ 18 ], and ethanol extract of Jaeumganghwa-tang [ 34 ]. The studies showed that YangXinDingJi significantly relieved HR damage via increasing the survival of H9C2 cardiomyocytes [ 33 ], inhibiting inflammatory cytokine expressions, reducing oxidative stress, and improving contractility in isolated rat cardiomyocytes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many traditional medicine formulas containing LIQ have been used to treat cardiovascular diseases, particularly ischemic heart diseases, such as Si-Miao-Yong-An decoction [ 32 ], Xuefu Zhuyu decoction [ 33 ], YangXinDingJi capsule [ 18 ], and ethanol extract of Jaeumganghwa-tang [ 34 ]. The studies showed that YangXinDingJi significantly relieved HR damage via increasing the survival of H9C2 cardiomyocytes [ 33 ], inhibiting inflammatory cytokine expressions, reducing oxidative stress, and improving contractility in isolated rat cardiomyocytes [ 18 ]. Ethanol extract of Jaeumganghwa-tang is relatively more efficacious at protecting against oxidative stress-induced muscle cell death [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation